Status Analysis of Flora from ”Cagar Alam – Pulau Sempu”, Malang - Hari Sulistyowati (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2008)
The Natural reserve of Sempu Island is one of protected areas in East Java. There are many endemic flora and fauna of Tropical Rain Forest. However, there is a rumor that the government will use this protected area as a County Jail. Based on this condition, it is important to investigate specifically the flora status of Sempu Island. The result can be used to give a lot of information about the endemic, existence, list of endangered, uniqueness, and also qualification values of the flora of Sempu Island as Biodiversity Species Richness of East Java and Indonesia. The plotting method of 1×1m2 , 5×5m2, and 10×10m2 were used to get the sample data of herbs, shrubs, and trees. The plots were placed systematically along transects. The result shows that 54.54% qualification values among the fifty five flora of Sempu Island were unique, 32.73% were very unique, and the rest were enough. Meaning, most of the flora was species that have high endangered and endemicness levels. Based on the IUCN (International Union for Conservation of Nature and Natural Resources) procedure conservation, therefore entire flora must be protected and conserved. Furthermore, the reserved island could not be converted as a County Jail.